Minimally invasive thread trigger digit release: a preliminary report on 34 digits of the adult hands. (November 2018) - Guo, Danqing; McCool, Logan; Senk, Alexander; Tonkin, Brionn; Guo, Joseph; Lytie, Rachel M.; Guo, Danzhu
The trigger finger release was performed in 34 digits (11 thumbs and 23 fingers) of 24 patients through the thread transecting technique with the tip-to-tip approach, in which a 22-gauge needle inserts into a 18-gauge needle when both needles are inside the hand, guiding the 22-gauge needle to exit the hand at the same access point of 18-gauge needle. We prospectively evaluated the effectiveness and functional recovery of these patients. In all 34 digits, triggering and locking were resolved, and complete extension and flexion occurred immediately following the release. There were no complications, such as incomplete release, neurovascular or flexor tendon or A2 pulley injury, infection, or tendon bow-stringing. Patients did not require prescription pain medications. Most patients used their hands to meet their basic living needs the same day of the procedure. The hand function evaluated with the Quick Disabilities of the Arm, Shoulder and Hand questionnaire, and scored 4 within 3 months. Level of evidence: II